Towards carbon monoxide sensors based on europium doped cerium dioxide - Ortega, P. P. [UNESP]; Rocha, L. S.R. [UNESP]; Cortés, J. A. [UNESP]; Ramirez, M. A. [UNESP]; Buono, C.; Ponce, M. A.; Simões, A. Z. [UNESP] (Elsevier, 2019)
Ce 1-(3/4)x Eu x O 2 (x = 0.00 and x = 0.08) thick films were prepared from nanoparticles synthesized by the microwave-assisted hydrothermal route, aiming their application as a carbon monoxide sensing material to prevent deaths caused by this highly toxic gas. XRD analysis revealed that the nanopowders are free from secondary phases and crystallize in the fluorite cubic structure, which is confirmed by Raman spectroscopy. The Eu-doped ceria film presented much higher response (S) values than pure ceria, demonstrating the higher sensitivity of the doped system to carbon monoxide, especially at 400 °C. Electrical measurements under different atmospheres revealed a remarkably fast carbon monoxide response time for the Eu-doped film when compared with the pure sample, proving that the introduction of europium cations in the ceria lattice as dopants has a positive effect on the carbon monoxide sensing properties.
Keywords: Carbon monoxide; Cerium dioxide; Gas sensor; Thick films